Effects of low intensity aerobic dance exercise on physiological and psychological well-being among working women - Johar, Mastura (2012)
The purpose of this investigation was to evaluate the effect of a 12-week low intensity aerobics dance exercise intervention in the treatment of physiological and psychological well-being among sedentary overweight employed women. Forty subjects were recruited from both the government and private sectors of Putrajaya, Bangi, Serdang and the surrounding community. Subjects were between the ages of 40 and 55 years, had a diagnosis of total stress score above the mean, were not enrolled in any exercise program over the period of one year (sedentary), overweight (Body Mass Index 25 and above) and had a cardiovascular endurance score below the mean. Subjects were randomly either assigned to a 12-week low intensity aerobics dance exercise intervention (“SenamSeri”) or a conventional aerobics dance exercise as the control group. A pretest-post test control research design was utilized. Both groups met for 50 minutes, three times a week (36 sessions). The Transactional Approach Multidimensional (Derogatis Stress Profile) examined Total Stress Score while Rosenberg’s Scale measured self-esteem; both were to assess changes in the psychological well-being. Additionally, physical fitness for health related components (ACSM) which included body composition, flexibility, muscle strength & endurance, cardiovascular endurance and the selected health parameters namely body mass index, resting heart rate and blood pressure were used to assess changes in the physiological well-being, respectively, as a result of the intervention at one, eight and 12-weeks. Statistical analysis included (group x time) repeated measures ANOVA and MANOVA to determine between and within group mean differences. The hypotheses of the thesis received significant support. When the results for physiological well-being variables were considered separately, the only difference to reach statistical significance, using a Bonferroni adjusted alpha level of 0.01, was body composition, F (1, 38) = 6.65, p < .01, eta square = .149, and Flexibility F (1, 38) =13.72, p < .01, eta square = .265. An inspection of the mean scores indicated that the treatment group reported an improvement for body composition (M =27.85, SD = 1.15) and for flexibility (M = 49.85, SD = 1.63) compared to the control group which reported body composition of (M = 27.85, SD = 1.14) and flexibility of (M = 49.85, SD = 1.63). Interestingly, the most obvious finding to emerge from this thesis was that the intervention group benefited significantly in terms of psychologically well-being, total stress score, F (1, 38) = 4.69, p < .05,quare = .11, and self-esteem F (1, 38) = 4.27, p < .05, eta square = .10. An inspection of the mean scores indicated that the treatment group “SenamSeri”reported lower levels of stress after 12 weeks (M = 39.00, SD = 2.36) and improvement in self-esteem (M = 34.45, SD = 1.18) than the control group which underwent the conventional aerobics dance exercise and charted a higher total stress level (M = 40.75, SD = 1.94) and lower self-esteem (M = 30.50, SD = 2.36). It is concluded that low intensity aerobics dance exercise intervention of “SenamSeri” had contributed greatly to the positive findings concerning the physiological and psychological well-being among sedentary overweight employed women.